An application of soil washing method for the remediation of contaminated soils by mining activities - Gökyay, Orhan (My University, 2001)
Toprağın ağır metallerle kirlenmesi ve buna bağlı olarak yeraltı sularının etkilenmesi birçok atık sahasının ortak problemidir. Yeraltı sularının kirlenmesine ek olarak, toprak kirliliği genellikle sahaların sınırlı kullanılmasına hatta bazen tarımsal veya diğer potansiyel kullanımları tamamen yasaklanmasına yol açmaktatdır. Ağır metallerin topraktan arıtılması çevre mühendisliği için en zor görevlerden biridir. Şu anda birçok arıtım metodu kullanılmakta veya geliştirlimektedir. Bunların amacı ağır metallerin etkili ve ekonomik biçimde yok edilmesidir. Bu metotlar topraktaki belli kirletici gruplarının arıtılması içindir örneğin ağır metaller, uçucu organanik maddeler, pestisitler fakat kullanılan metotlar bütün kirleticileri bir anda yok edememektedirler ama toprak yıkama metodu kirleticilerin hepsini bir seferde yok eder, kolay uygulanır, etkilidir ve ekonomiktir. Bu çalışmada, özellikle Cu ve Fe metallerinin arıtılması üzerinde duruldu, bunların yanında Cd ile de ilgielenildi. Bu amaçla, ilk yapılan toprak karakterizasyonundan sonra, kesikli arıtım ve kolon deneyleri Kuzey Kıbrıs, Lefke'deki eski bir maden fabrikasından alınan toprak numunelerine üzerinde uygulandı. Yapılan deneylerden alınan sonuçlar gösterdiki en iyi arıtım EDTA solüsyonu ile sağlandı. 40 gr toprak için 500 ml, 0.1 M EDTA en iyi sonuçları verdi. Bunun yanında optimum yıkama zamanı ise 3 saat olarak bulundu.

Toxic heavy metal contamination of soil and subsequent potential fouling of ground water is a common problem at many hazardous waste sites. In addition to contributing to pollution of groundwaters, soil contamination often results in restricted utilization of the site and, in some cases, a complete prohibition on cultivation or other potential use of the area. The clean-up of soils contaminated with heavy metals is one of the most difficult tasks for environmental enginneering. Currently, many treatment processes have been developed or are now being developed which can remediate contaminated soils in an effective and economic manner. However, these processes have been found to be successful only for the removal of specific groups of contaminants from soils; either metals, volatile organic compounds, or pesticides and herbicides, and are not effective to remove the mixed pollutants from soils, resulting in expensive remedial operations but soil washing technique can remove all in a one step process and it is easy to implement, efficient and economical. In this study, it was focused on the removal of especially Cu and Fe and also Cd metals. For this purpose, after initial soil characterization, batch shaker tests and column analysis were conducted for the soil sample taken from an old mining site at Lefke, Northern Cyprus. From the experiments carried out, it was concluded that best solution for removal of these heavy metal is EDTA solution with a molarity of 0.1 and a volume of 500 ml is used per 40 gr of contaminated soil. Moreover, the optimum washing time for this soil is found as 3 hours.
Keywords: Çevre Kirliliği; Çevresel sorunlar; Kirlilik; Toplumsal sorunlar